Direct Trifluoromethoxylation without OCF3‐Carrier through In Situ Generation of Fluorophosgene. Issue 22 (8th June 2021) - Saiter, Jérémy; Guérin, Thomas; Donnard, Morgan; Panossian, Armen; Hanquet, Gilles; Leroux, Frédéric R.
Abstract: Owing to the high interest in the OCF3 group for pharmaceutical and agrochemical applications, trifluoromethoxylation received great attention in the last years with several new methods for this approach towards OCF3 ‐comprising compounds. Yet, it most often requires the beforehand preparation of specific F3 CO − transfer reagents, which can be toxic, expensive, unstable, and/or generate undesired side‐products upon consumption. To circumvent this, the in‐situ generation of gaseous fluorophosgene from triphosgene, its conversion by fluoride into the OCF3 anion, and the direct use of the latter in nucleophilic substitutions is an appealing strategy, which, although recently approached, has not been fully exploited. We disclose herein our efforts towards this aim. Abstract : An efficient atom economical trifluoromethoxylation method was developed with no need for trifluoromethoxylation reagent. This method relies on the in‐situ generation of fluorophosgene and its conversion into OCF3 anion to achieve nucleophilic substitution on a series of alkyl iodides.